Metagenomic analysis reveals the virome profiles of Aedes albopictus in Guangzhou, China - Xu, Ye; Xu, Jiabao; Liu, Tong; Liu, Peiwen; Chen, Xiao-Guang (Frontiers in Cellular and Infection Microbiology, 2023)
Aedes albopictus, the most invasive mosquito in the world, is a known vector for many important viral pathogens such as Dengue virus, Zika virus, and Chikungunya virus. In this study, we employed small RNA sequencing and bioinformatics to characterize the virome of nine pools of Ae. albopictus in China, which included female adults, male adults, and larvae. A total of five known viruses and 21 novel virus-associated contigs were identified. Wenzhou sobemo-like virus 4 was found in 8 pools, indicating its dominance in Ae. albopictus. Our research analyzed the virus metagenomics in different sex and lavrval Ae. albopictus and provided valuable information on its virome. This study will help in identifying potential pathogens that could pose a threat to public health.